2017
DOI: 10.1186/s12885-017-3391-5
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of local control in Ewing sarcoma: analysis of the first Brazilian collaborative study group – EWING1

Abstract: BackgroundRelapse in localized Ewing sarcoma patients has been a matter of concern regarding poor prognosis. Therefore, we investigated the impact of local control modality (surgery, surgery plus radiotherapy, and radiotherapy) on clinical outcomes such as survival and recurrence in patients with non-metastatic Ewing sarcoma treated on the first Brazilian Collaborative Group Trial of the Ewing Family of Tumors (EWING1).MethodsSeventy-three patients with localized Ewing sarcoma of bone aged < 30 years were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
1
15
1
2
Order By: Relevance
“…The effect of radiation therapy on the prognosis for metastatic ES is unclear. Previous studies have shown that patients with ES who received only radiation therapy as the local treatment, had significantly reduced OS and CSS compared with patients who underwent surgery alone [24,29,30], which is consistent with the findings of the present study. However, some studies have reported that radiation therapy alone improved local control and survival that was comparable to surgery [3133].…”
Section: Discussionsupporting
confidence: 93%
“…The effect of radiation therapy on the prognosis for metastatic ES is unclear. Previous studies have shown that patients with ES who received only radiation therapy as the local treatment, had significantly reduced OS and CSS compared with patients who underwent surgery alone [24,29,30], which is consistent with the findings of the present study. However, some studies have reported that radiation therapy alone improved local control and survival that was comparable to surgery [3133].…”
Section: Discussionsupporting
confidence: 93%
“…In this study; site of the tumor had no significant effect and this was contrary to Karski EE et al also no significant impact of surgery on LRFS which wasn't comparable to Ricardo G et al [11] that detected a 5-year event free survival of 30.8% for patients received definitive RT, 64.1% for surgery plus RT and 71.7% for surgery alone. 3-year LC in our study was 35% which was comparable to DuBois SG [1] that denoted high incidence of local relapses in those received definitive RT and in ours; the local control was low as no complete surgical excision was done.…”
Section: Discussioncontrasting
confidence: 95%
“…Small round cell tumors such as Ewing's sarcoma family usually respond well to radiation 24 . Therefore, radiotherapy is frequently indicated for primary and adjuvant treatment of PNET.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, there have been no randomized studies comparing surgery and radiotherapy in Ewing tumors. Some studies reported that radical radiotherapy as the only local treatment for Ewing's sarcoma predicted adverse survival or local control 24,27,28 . However, in these studies, the choice of local treatment was influenced by multiple factors and thus non-randomized.…”
Section: Discussionmentioning
confidence: 99%